2014
DOI: 10.12669/pjms.304.4807
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Discomfort of Dental Rehabilitation under General Anesthesia

Abstract: Objective: To find out postoperative discomfort in children undergoing dental rehabilitation under general anesthesia (DRGA). Methods: This study involved 78 (4 to 10 year-old) healthy patients who were scheduled for DRGA and were needed extensive dental treatment because of severe caries, and showed high dental fear and/or behavioral management problems. The children had to be fit for DRGA administration by fulfilling the American Society of Anesthesiologists physical status I or II and no associated mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
1
25
1
1
Order By: Relevance
“…Under GA all required treatments are performed in a single session in a hospital environment providing efficient services in a safe mode ( 4 , 8 , 15 ). Moreover, GA is one modality to ensure that the child received effective pain control ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under GA all required treatments are performed in a single session in a hospital environment providing efficient services in a safe mode ( 4 , 8 , 15 ). Moreover, GA is one modality to ensure that the child received effective pain control ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of pediatric patients report complaints following dental GA procedure in different severity ( 23 ). Dental pain, difficulty in eating, nasal bleeding, throat discomfort, nose discomfort, sleep alteration, weakness, drowsiness, dehydration, fever, nausea, vomiting, hoarseness, diarrhea and constipation are several reported postoperative discomforts ( 8 , 23 ). Post-operative pain is the most common complaint reported ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric patients that undergo dental treatment under GA often complain of post-operative complications, which include dental pain, difficulty in eating, nasal bleeding, throat discomfort, nose discomfort, sleep alteration, weakness, drowsiness, dehydration, fever, nausea, vomiting, hoarseness, diarrhea, and constipation. [17][18][19] PB might provide a better option than other dental treatments as it is cost-effective, helps stabilize and calm patients, and reduces complications and risks during dental treatment. 20 Our findings showed that 63.2% of respondents agreed that PB was an effective behavioral management technique.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative patient discomfort differs with the type of surgery. In oral surgery, discomfort has been extensively taken into account as a component of good outcome, for example, in root canal surgery, [10][11][12][13][14][15][16][17] orthodontic procedures, [18] third molar surgery, [19][20][21][22] treatment of caries, [23,24] soft-tissue surgery, [25] and frenectomy. [26] In some surgical procedures, pain is not the main disturbing postoperative symptom.…”
Section: Introductionmentioning
confidence: 99%